Caraterização da membrana da casca do ovo de galinha para a produção de microcápsulas de hidrogel pela técnica de gelificação iônica - Meneses, Camila Gomes Dantas (2024)
Eggs are an affordable source of protein and their production in Brazil has increased over the years. Example: Egg consumption as a cost effective proteine source has seen a market rise in recent years. This growth has led to an increase in waste from the industry, primarily from eggshells, which make up to 11% of an egg’s total weight. Along with the shells, the membranes have nutritional value as they are sources of proteins, including collagen, a fibrous protein formed by the amino acids glycine, proline and hydroxyproline. Collagen supplementation is highly recommended due to the decrease in its natural production by the body at the beginning of adulthood. The eggshell membrane can be used as a strategy for this replacement, since type I, V and X collagens are present in its composition. In this context, this study aimed to microencapsulate the eggshell membrane using the ionic gelation technique, a simple and lowcost alternative that will preserve the existing collagen in the membrane. The eggshells were collected in a food industry located in the city of Aracaju/SE. The membranes and microcapsules underwent comprehensive characterization, including physical analyses (yield, size, weight, water activity, and color), physical-chemical analyses (moisture, ash, pH, total proteins, collagen, hydroxyproline, proline, glycine), as well as Infrared Spectroscopy with Transformation Fourier (FTIR), and microbiological analyses for thermotolerant coliforms and Salmonella spp. The analyzes were carried out in triplicate and the values found were expressed as the mean ± standard deviation. The results obtained indicated the absence of Salmonella in 25g of membrane and thermotolerant coliforms (<3 MPN/g) for samples subjected to heat treatment, as recommended by legislation. As for the yield of the membrane removal process, it presented a favorable value (13.07%), which makes its reuse viable. When evaluating the results of total and collagen proteins of the microcapsule (1.18% ± 0.04 and 0.65%) compared to those of the membrane (86.80% ± 2.17 and 8.17% ± 0.25) the need to offer a new means of storing the membrane was identified, aiming for greater nutritional use. Therefore, 100 mg of eggshell membrane was encapsulated in colorless gelatin capsule nº1. The results of the quantification of amino acids present in the membrane were hydroxyproline (1.02% ± 0.02), proline (10.3% ± 0.12) and glycine (4.72% ± 0.02). Finally, FTIR analyzes showed the presence of amines and amides in the eggshell membrane particle. This study resulted in the development of a new product with high nutritional value, encouraging the food and/or pharmaceutical industry to develop new products with added value.